Central themes of the relationship between pesticides and cancer: A systematic review of the literature - Aguiar , João Carlos Belarmino; Silva, Luciana Santos Costa Vieira da; Silva, Wesley Vieira da; Curado, Fernando Fleury; Lima, Paola Hernandez Cortez; Pereira , Lidiane de Almeida; Silva, Bianca Lima; Rita, Luciana Peixoto Santa; Pinto, Ibsen Mateus Bittencourt Santana (Seven Editora, 2023)
Objective – to identify central themes in the relationship between pesticides and cancer associated with rural areas, agriculture or agribusiness, through a Systematic Literature Review. Methodology – The research is exploratory, with a quantitative approach for bibliometric analysis and qualitative for the supervision of articles in the final corpus and the discussion of central themes. Results - The analysis of corpus indicators demonstrated that the topic can be considered recent and with a tendency to grow. The coupling bibliographic of the corpus, using the VOSviewer software, showed low quantitative and intensity connections. The thematic map highlights emerging central themes about “breast cancer”, “childhood cancer” and “nervous system”, niche themes such as “DNA damage”, basic themes about “environmental protection” and motors, “health study”, “risk of cancer” and “exposure to pesticides”. Methodological contributions – Identification of themes with reduced bias by centrality and density statistics, which may represent advances in knowledge. Social and environmental contributions – The discussion of the central themes points to the approach of research techniques such as biomarkers and evidence mapping, exposure to pesticides associated with other areas, such as gardens, parks, urban areas, which can cause damage to health beyond the cancer, such as lung and coronary diseases, DNA damage, reporting strategies to reduce these risks through the use of PPE, distance from homes to places that use pesticides, training of farmers. However, these measures seem insufficient, as State regulation allows the use of pesticides within certain limits, generally exceeded, which contributes to damage to health and the environment. DOI:https://doi.org/10.56238/sevened2023.004-048